Changes in the Physicochemical Parameters of Surface Water Over a Period of 35 Years - Lovorka Gotal Dmitrovic; Darijo Čerepinko (Journal of Sustainable Development of Energy, Water and Environment Systems)

(untitled)
The research was based on the change in physical and chemical parameters of surface water over 35 years. Surface water (river) flows in a sensitive area according to the Nitrate Directive. Statistical analysis was used to examine the connection between changes in the quality of surface water and the construction of municipal waste water drainage systems, changes in agricultural production and demographic changes. The research highlights significant positive changes in surface water quality, primarily attributed to the implementation of sewage systems, municipal wastewater treatment, and reduced agricultural pollution. Regulatory modifications in agriculture, demographic transformations, and the influence of the Nitrates Directive on agricultural output have contributed to the decline in pollution levels in the river.